Targeting Innate Immunity to Enhance the Efficacy of Radiation Therapy - Dar, Tahir B.; Henson, Regina M.; Shiao, Stephen L. (Frontiers in Immunology, 2019)
Radiation continues to play a major role in the treatment of almost every cancer type. Traditional radiation studies focused on its ability to damage DNA, but recent evidence has demonstrated that a key mechanism driving the efficacy of radiation in vivo is the immune response triggered in irradiated tissue. Innate immune cells including macrophages, dendritic cells, and natural killer cells are key mediators of the radiation-induced immune response. They regulate the sensing of radiation-mediated damage and subsequent radiation-induced inflammation. Given the importance of innate immune cells as determinants of the post-radiation anti-tumor immune response, much research has been devoted to identify ways to both enhance the innate immune response and prevent their ability to suppress ongoing immune responses. In this review, we will discuss how the innate immune system shapes anti-tumor immunity following radiation and highlight key strategies directed at the innate immune response to enhance the efficacy of radiation.